Prenatal diethylstilbestrol exposure and cancer risk in women. (10th November 2017) - Troisi, Rebecca; Hatch, Elizabeth E.; Titus, Linda; Strohsnitter, William; Gail, Mitchell H.; Huo, Dezheng; Adam, Ervin; Robboy, Stanley J.; Hyer, Marianne; Hoover, Robert N.; Palmer, Julie R.
Abstract : In the Diethylstilbestrol [DES] Combined Cohort Follow‐up, the age‐ and calendar‐year specific standardized incidence ratio [SIR] for clear cell adenocarcinoma [CCA] was 27.6 (95% confidence interval [CI] 7.51‐70.6) for the exposed women. The SIR for breast cancer was 1.17 (95% CI 1.01‐1.36) and the hazard ratio [HR] adjusted for birth year and cohort for comparison with the unexposed was 1.05 (95% CI 0.79‐1.41). The SIR for pancreatic cancer was 2.43 (95% CI 1.21‐4.34) and the adjusted HR for comparison with unexposed women was 7.16 (95% CI 0.84‐61.5). There was little evidence of excess risk for other sites. There appeared to be a deficit in risk for endometrial cancer among the exposed (SIR 0.61; 95% CI 0.35‐0.98), and an excess in the unexposed (SIR 1.55; 95% CI 0.95‐2.40); the adjusted HR was 0.45 (95% CI 0.22‐0.93) for the internal comparison. There was no overall excess cancer risk in exposed women compared with general population rates (1.06; 95% CI 0.95‐1.17) or with unexposed participants (adjusted HR 1.03; 95% CI 0.84‐1.25). These data do not support the suggestion that there is a diathesis of cancers in DES exposed female offspring The excess risk of breast and pancreatic cancers that we observed is concerning and warrants continued follow‐up and mechanistic investigation. Environ. Mol. Mutagen. 60:395–403, 2019. Published 2017. This article is a US Government work and is in the public domain in the USA.